Препятствия имплементации нормы о незаконном обогащении в национальное право - Михайленко Дмитро Григорович; Mychailenko D.G.; Михайленко, Дмитрий Григорьевич (My University, 2015)
В статье исследуются теоретические и нормативные положения национальных систем права Украины и Казахстана, которые могут блокировать полноценную реализацию нормы о незаконном обогащении (в смысле ст. 20 Конвенции ООН против коррупции). Устанавливается, что основным препятствием введения в правовые системы Украины и Казахстана исследуемого антикоррупционного инструмента является принцип презумпции невиновности. Обосновывается вывод о необходимости изучения возможности и целесообразности частичного ограничения действия этого принципа нормой о незаконном обогащении в целях противодействия коррупции.

The article examines theoretical and normative provisions of national legal systems of Ukraine and Kazakhstan, that may block full realization of the legal norm on illicit enrichment (in the meaning of the Art. 20 of the UN Convention against corruption), and defines its actual correspondence to the composition of this crime. In the article the author defines that the main obstacle for the introduction of the instrument, examined in the article to the legal systems of Ukraine and Kazakhstan is in the principle of presumption of innocence. The author substantiates the conclusion on the necessity to study of possibilities and appropriateness of partial restriction of this principle by the norm on illicit enrichment, with the purpose of countering corruption both, in Ukraine and Kazakhstan. It is shown that arguments against introduction of the norm on illicit enrichment themselves cannot prevent it.
Михайленко Д. Г. Препятствия имплементации нормы о незаконном обогащении в национальное право / Д. Г. Михайленко // Право и государство=Кұқық және мемлекет. - 2015. - № 4 (69). - С. 55-61.
Keywords: коррупция; коррупционные преступления; Концепция ООН против коррупции; многорубежная модель уголовно- правового противодействия коррупции; незаконное обогащение; принцип презумпции невиновности; бремя доказывания; презумпции в уголовном праве; corruption; corruption offences; UN Convention against corruption; multi frontier model of criminal and legal counteraction against corruption; illicit enrichment; principle of presumption of innocence; proof burden; presumptions in criminal law